(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND:Miscarriage is a common reproductive health issue affecting up to 26% of pregnancies globally. Despite its high prevalence, the psychological consequences are often under-recognized, particularly in low- and middle-income countries. This study aims to assess the levels of depression, anxiety, and stress among women following miscarriage and identify associations with demographic and clinical variables. OBJECTIVE:To evaluate the mental health impact of miscarriage in terms of depression, anxiety, and stress, and determine the relationship between psychological morbidity and selected patient characteristics. METHODS:This cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Northwest General Hospital, over a six-month period. A total of 77 women aged 15–49 years who experienced miscarriage within the past seven days were enrolled using non-probability consecutive sampling. Exclusion criteria included ectopic pregnancy, pre-existing psychiatric illness, serious medical conditions, and recent major life stressors. Data were collected using a predesigned demographic proforma and the Depression, Anxiety, and Stress Scale (DASS-21). Chi-square test and independent sample t-test were applied to assess statistical significance, with p<0.05 considered significant. RESULTS:Out of 77 participants, 37.7% reported moderate to severe depression, 41.6% reported moderate to severe anxiety, and 33.8% experienced significant stress. Statistically significant associations were observed between psychological morbidity and factors such as unplanned pregnancy, lack of social support, and low socioeconomic status (p<0.05). CONCLUSION:Miscarriage is associated with a high burden of psychological distress, including depression, anxiety, and stress. Routine mental health screening and timely psychological support are essential for women experiencing pregnancy loss, particularly those with identifiable risk factors